Pakistani Learners’ Perceptions of Portfolio Assessment as a Motivational Factor in Learning English as a Foreign Language - Majeed, Aamir; Maqsood, Maida; Labony, Mahmuda Akther (Pakistan Languages and Humanities Review, 2023)
The importance of aligning assessment methods with EU standards for efficient language acquisition has grown in response to the dynamic changes in educational needs. The purpose of the study is to investigate how students’ motivation to learn English as a foreign language (EFL) is influenced by portfolio-based assessment. This study recognizes the difficulties teachers encounter when implementing effective classroom instruction and assessment strategies, and it responds to the increasing interest in assessing student performance. The study aims to collect student opinions regarding portfolio-based rewards for EFL coursework and investigates the effects of this evaluation technique on motivation. Using online surveys, graduate students at "The Linguists," a Sialkot-based English language institute, participated in this qualitative study. The goal of the qualitative lens of inquiry was to learn how students perceived the motivational impact of portfolio assessments. The questionnaire included both closed-ended and open-ended questions to find out how students felt about the impact of portfolio assessments on their motivation and interest in learning. Analysis showed that portfolio evaluations had a favorable impact on students’ motivation to learn EFL, independence, and critical thinking. Pupils highlighted how portfolios promoted self-evaluation and increased engagement, which showed promise for improved learning outcomes. They saw portfolios as essential for identifying their advantages and disadvantages, encouraging self-reliance, and developing reflective abilities. The study, which noted students’ increasing independence over time, emphasized the necessity of teachers providing initial guidance in the use of portfolios.